Brain Activation Differences of Six Basic Emotions Between 2D Screen and Virtual Reality Modalities - Jialan Xie; Ping Lan; Shiyuan Wang; Yutong Luo; Guangyuan Liu (IEEE Transactions on Neural Systems and Rehabilitation Engineering)
To our knowledge, it has been widely studied in Screen-2D modality for the six basic emotions proposed by Professor Paul Ekman, but there are only studies on their positive and negative valence in VR-3D modality. In this study, we will investigate whether the six basic emotions have stronger brain activation states in VR-3D modality than in Screen-2D modality. We designed an emotion-inducing experiment with six basic emotions (happiness, surprise, sadness, fear, anger, and disgust) to record the electroencephalogram (EEG) signals during watching VR-3D and Screen-2D videos. The power spectral density (PSD) was calculated to compare the brain activation differences between VR-3D and Screen-2D modalities during the induction of the six basic emotions. The results of statistical analysis of the relative power differences between VR-3D and Screen-2D modalities for each emotion revealed that both happiness and surprise presented greater differences in the $α $ and $γ $ frequency bands, while sad, fear, disgust and anger all presented greater differences in the $α $ and $θ $ frequency bands, which are mainly observed in the frontal and occipital regions. On the other hand, the six emotions all yielded satisfactory classification accuracy (above 85%) by classification from a subset of power feature of the brain activation states in the same emotion between the two modalities. Overall, there are significant differences in the induction of same discrete emotions in VR-3D and Screen-2D modalities, with greater brain activation in VR-3D modalities. These findings provide a better understanding about the neural activity of discrete emotional tasks assessed in VR environments.